3D Printer Chocolate Cake Berbasis Arduino - Andrean George Wibisono; Bobi Kurniawan (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2020)
3D Printing is an evolution of printing technology, which is capable of producing or producing and designing sophisticated structures in a single unit. 3D Printing is one of the fabrication processes of Fused Deposition Modeling (FDM), which is Additive Manufacturing (AM) technology, which works with addition of ingredients layer by layer. In the industrial world, 3D Printing is very popular because for the manufacture of prototypes that usually require a long time can be made in a shorter time. This greatly affects the costs incurred in producing a quality product. Based on this background, this final project assembles a Prusa i3 type 3D Printer tool. This tool will be used to print 3-dimensional products derived from CAD design so that it can help lecturers or students in the project work such as research, robot components, modules and other objects. The thing that must be considered in product printing is the printed raw material that will be used. In writing this final task will be discussed about the tools and materials needed to assemble 3D Printers, design products, determine the raw materials for printing, tool operation methodology to the final results that will be made by 3D Printers. Keyword Â: 3D Printer, 3-dimensions